Diferentes concentrações de ácido fluorídrico e seu efeito na resistência flexural de uma cerâmica vítrea à base de dissilicato de lítio - Prochnow, Catina (2015)
This study aimed to evaluate the effect of different hydrfluoric acid (HF) concentrations on the flexural strength of a lithium disilicate based glass ceramic. Ceramic bar-specimens (14x4x1.2mm) were produced from ceramic blocks (e.max CAD, Ivoclar Vivadent), according to ISO 6872. The ceramic bars were randomly divided into 5 groups (n=23): SC (control) without treatment, HF1, HF3, HF5 e HF10 conditioned for 20 s with different acid concentrations: 1%, 3%, 5% e 10%, respectively. The etched ceramic surfaces were evaluated in a scanning electron microscope (SEM) and atomic force microscope (AFM). The roughness of treated surfaces was measured and the specimens were submitted to the 3-point flexural strength testing. Data were analyzed using 1-way ANOVA, Tukey‟s test (α=0.05), Pearson correlation and Weibull analyzis (modulus and characteristic strength). No statistical difference was found amoung groups for roughness and flexural strength, and the correlation between the data roughness and flexural strength was not statistically significance. The structural reliability (Weibull modulus) was similar among the tested groups, however, HF1 presented characteristic strength greater than HF10. The conditioning with different HF concentrations did not affect the surface roughness anfd flexural strength to a lithium disilicate based glass ceramic, when compared to untreated ceramic, regardless of the HF concentration used.